UJI EFEKTIFITAS AGENSIA HAYATI DALAM MENGENDALIKAN PENYAKIT LAYU BAKTERI Ralstonia solanacearum DAN MENINGKATKAN PERTUMBUHAN SERTA HASIL TANAMAN CABAI (Capsicum annum) - Kasidal Kasidal; Noor Aidawati; Dewi Erika Adriani (EnviroScienteae, 2019)
Chili is an important commodity for most people, because of its function in terms of improving taste and appetite. Chili was seriously developed with the support of government funds for chili farmers. The development of chili plants, has enough obstacles, especially wich caused by plant disturbing organisms whether it is pests or diseases. The important organism that disturbs chili is wilting caused by Ralstonia solanacearum. In South Kalimantan, this disease reportedly attacked chilies spread in the districts of Banjar, Banjarbaru, Barito Kuala, Tapin, Hulu Sungai Tengah and Balangan with a cumulative attack area of 15,7 ha on 2017 (South Kalimantan BPTPH Database). This disease is important because of the nature of the attack which can cause the plants to wilt suddenly all part of the plant. Plants wich attacked by bacterial wilt cannot be cured. The effort that can be done in prevention before pathogens infect the plants (Sastra, 2004). One way to overcome this problem is biological control using biological agents from the type of antagonistic bacteria Bacillus spp, Pseudomonas fluorescens, and type of antagonistic fungus Trichoderma spp. From three biological agents proven able to inhibit the development of R. solanacearum in vitro which produces a zone of inhibition as wide as 13,5 mm for Bacillus spp, 22,25 mm for Pseudomonas fluorescens and 8,42 mm for Trichoderma spp. and can increase plant height growth, chili weight, root weight, wet weight, and dry weight plants. Trichoderma spp as the best biological agents for increasing chili growth and yield.